Challenges and Opportunities to Use Biowaivers to Compare Generics in China - Zuo, Jieyu (Springer US, 2014)
Biowaivers for class I drugs according to the biopharmaceutics classification system (BCS) were first introduced in 2000. The in vitro equivalence can be used to document bioequivalence between products. This study compared the in vitro dissolution behavior of two BCS class I drugs, amoxicillin and metronidazole, which are sold in China. Identifying a reference product on the Chinese domestic market was impossible. Three 250-mg and two 500-mg amoxicillin capsules and four metronidazole tablet products were tested. None of the amoxicillin products and three of the four metronidazole tablets were found to be equivalent to each other when the same strengths were compared. The bioequivalence of products that fail the in vitro test can be established via in vivo clinical studies which are expensive and time consuming. Establishing nationally or globally accepted reference products may provide regulatory agencies with an efficient mechanism approving high quality generics.